Inhibition of HTLV-1 Infection by HIV-1 First- and Second-Generation Integrase Strand Transfer Inhibitors - Barski, Michał S.; Minnell, Jordan J.; Maertens, Goedele N. (Frontiers in Microbiology, 2019)
More than 10 million people worldwide are infected with the retrovirus human T-cell lymphotropic virus type 1 (HTLV-1). Infection phenotypes can range from asymptomatic to severe adult T-cell leukemia/lymphoma (ATLL) and HTLV-1-associated myelopathy. HTLV-1, like human immunodeficiency virus type 1 (HIV-1), is a blood-borne pathogen and viral infection happens in a similar fashion, with the major mode of transmission through breastfeeding. There is a strong correlation between time of infection and disease development, with a higher incidence of ATLL in patients infected during childhood. There is no successful therapeutic or preventative regimen for HTLV-1. It is therefore essential to develop therapies to inhibit transmission or block the onset/development of HTLV-1 associated diseases. Recently, we have seen the overwhelming success of integrase strand transfer inhibitors (INSTIs) in the treatment of HIV-1. Previously, raltegravir was shown to inhibit HTLV-1 infection. Here, we tested FDA-approved and two Phase II HIV-1 INSTIs in vitro and in a cell-to-cell infection model and show that they are highly active in blocking HTLV-1 infection, with bictegravir (EC50 = 0.30 ± 0.17 nM) performing best overall. INSTIs, in particular bictegravir, are more potent in blocking HTLV-1 transmission than tenofovir disproxil fumarate, an RT inhibitor. Our data suggest that HIV-1 INSTIs could present a good clinical strategy in HTLV-1 management and justifies the inclusion of INSTIs in clinical trials.